O caráter monológico da racionalidade neoclássica - Prado, Eleutério F. S. (Estudos Econômicos (São Paulo), 1996)
This paper pays attention to the demosntrative character of racionality concept employed in neoclassical theory, putting in question its apparent triviality. It examines texts of Jevons, Walras, Marshall and Robbins which are viewed as representatives of neoclassical theory. In order to enlighten its salient feature, this usual notion is compared with the aristotelian concept of racionality. While the former is shown to be instrumental apodictical and monological, the latter is shown to be expressive, prudential and dialogical. While this ultimate concept of racionality emerged from the ethical and political life in the polis, the other emerged from the systemic and individualistic life in the markets and organizations. From this point of view, the modern science and the ancient philosophy only shapped them by the time, making them cleary visible and rigorous. In order to explain these two historical occurences, the paper relies on Habermas evolutionary theory of society.